Pengaruh kepemimpinan kepala sekolah dan kompetensi guru terhadap prestasi belajar siswa Sd muhammadiyah baturan Tahun ajaran 2015/2016 - Kurniawati, Fajar, Minsih, S.Ag., M.Pd (2016)
This study aims to determine: (1) To determine whether there is influence of school leadership on student chievement SD Muhammadiyah Baturan the academic year 2015/2016. (2) To determine whether there is influence between competence of teacher on students achievement SD Muhammadiyah Baturan the academic year 2015/2016. (3) to determine the significant relationship between school leadership and teacher competence on student achievement SD Muhammadiyah Baturan the academic year 2015/2016. Research includes quantitative research models analytical survey. Population in this study were students in grade IV and V SD Muhammadiyah Baturan. The technique of collecting data using questionnaires and documentation techniques. Test Instruments used Test Validity and Test Reliability. Data were analyzed using t-test technique which preceded the prerequisite test analysis is the normality test and linearity test. Based on the research can be concluded that there is significant influence between school leadership and teacher competence on student achievement SD uhammadiyah Baturan Academic Year 2015/2016 amounting to 61,39%.